1998
DOI: 10.1007/s11661-998-0132-z
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic deformation behavior of high-purity titanium single crystals: Part II. Microstructure and mechanism

Abstract: Strain-controlled cyclic tests have been conducted on high-purity titanium single crystals with different orientations. The fatigue mechanisms of the titanium crystals were studied by means of a scanning electron microscope (SEM) and a transmission electron microscope (TEM). It was found that single slip lines, wavy slip lines, double slip lines, twins, and associated slip lines occurred in differently oriented single crystals. A new type of fractographic morphology, parallel traces, was observed. Dislocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 17 publications
0
9
0
5
Order By: Relevance
“…Unlike fcc materials that usually have only one slip mode f111g 10 " 1 À Á ; there are at least four reported slip modes in a-Ti: three instances of 0001 f g 1 " 210 basal slip, three of 10 " 10 È É 1 " 210 prismatic slip, six of 10 " 11 È É 1 " 210 pyramidal hai slip, and twelve of 10 " 11 [26,27] Among them, prismatic slip has the lowest CRSS, and is therefore the primary slip mode in a-Ti. [26][27][28][29][30] Table I summarizes the material parameters used in this model. Basal, prismatic, and pyramidal c þ a h i are the three slip modes that were included in the current simulation.…”
Section: A Constitutive Modelmentioning
confidence: 99%
“…Unlike fcc materials that usually have only one slip mode f111g 10 " 1 À Á ; there are at least four reported slip modes in a-Ti: three instances of 0001 f g 1 " 210 basal slip, three of 10 " 10 È É 1 " 210 prismatic slip, six of 10 " 11 È É 1 " 210 pyramidal hai slip, and twelve of 10 " 11 [26,27] Among them, prismatic slip has the lowest CRSS, and is therefore the primary slip mode in a-Ti. [26][27][28][29][30] Table I summarizes the material parameters used in this model. Basal, prismatic, and pyramidal c þ a h i are the three slip modes that were included in the current simulation.…”
Section: A Constitutive Modelmentioning
confidence: 99%
“…[1][2][3] Experiments on single-crystal high-purity titanium showed that the critical resolved shear stress for prismatic slip is much lower than that of other slip modes: 0001 f g 1 " 210 basal slip, 10 " 11 È É 1 " 210 pyramidal hai slip, and 10 " 11 È É 2 " 1 " 1 " 3 pyramidal hc+ai slip. [4] Nevertheless, the prismatic slip mode alone is not sufficient to accommodate an arbitrary plastic strain, which, according to the von Mises criterion, requires five independent slip systems. [5] As a result, nonprismatic slip and deformation twinning are also necessary to achieve significant plastic deformation in polycrystalline titanium.…”
mentioning
confidence: 99%
“…When the microstructural observations shown in Part II of this study [22] are combined with the geometric analysis results, a map of the orientation de- pendence of the cyclic deformation modes in titanium single crystals can be prepared ( Figure 6). Partic-2 ularly, the contribution of {10 0} slip to cyclic plastic de-1 formation should be weighted against with the other deformation modes.…”
Section: Discussionmentioning
confidence: 99%